The Economy of the Organizations in the founding competence of the Ministry of Education, Science, Research and Sports of the Slovak Republic in 2021: are the public finances managed efficiently? - Zuzana STOLIČNÁ; Jana BARJAKOVÁ (Communications of International Proceedings, 2022)
This paper is focused on the management of organizations under the founding authority of the Ministry of Education, Science, Research and Sports of the Slovak Republic in 2021. The paper provides an evaluation of the performance of these organizations through the analysis of concluded "contracts", which are the basic management tool for these organizations for the year. The aim of the article is to evaluate the management of subordinate organizations of the Ministry of Education, Science, Research and Sports of the Slovak Republic in 2021 through the impact on the state budget and to find out whether the management of public funds and the performance of the tasks entrusted was effective. Within the data processing, several methods of data analysis were applied, as well as practical experience from working in the government department. The main findings are that the organizations have properly documented the use of the funds provided to fulfill the tasks in 2021, but compared to 2020 they performed fewer tasks, but more demanding on the state budget and significantly more demanding on drawing on Euro funds.
Keywords: ministry; budgetary and contributory organizations; management; governance; public administration